Propeller flap for complex distal leg reconstruction: a versatile alternative when reverse sural artery flap is not feasible (2015)
Reverse sural artery fasciocutaneous flap has become a workhorse for the reconstruction of distal leg soft tissue defects. When its use is not feasible, perforator-based propeller flap offers a better, easier, faster, and cheaper alternative to free flap. We present our experience with two men both aged 34 years who sustained Gustilo 3B injuries from gunshot. The donor area for reversed sural artery flap was involved in the injuries. They had early debridement, external fixation, and wound coverage with perforator-based propeller flaps. The donor sites were covered with skin graft. All flaps survived. There were minor wound edge ulcers due to the pressure of positioning that did not affect flap survival and the ulcers healed with conservative management. Perforator-based propeller flap is a versatile armamentarium for reconstruction of soft tissue defects of the distal leg in resource-constrained settings, especially when the donor area for a reverse flow sural flap artery is involved in the injury.